Ultra-broadband sound absorption in a compact multi-chamber micro-perforated panel absorber with varying depths - Bennett, Gareth (My University, 2024)
This study presents an enhanced multi-chamber micro-perforated panel absorber (MC-MPPA) with varying sub-chamber depths, offering ultra-broadband low-frequency sound absorption. Traditional micro-perforated panel absorbers are constrained by a limited bandwidth, necessitating impossibly small perforations for optimal low-frequency absorption. Our innovative design addresses these constraints with a lightweight, compact panel structure that uses varied chamber depths and unique porosities. Using the two-point impedance method from graph theory, an MC-MPPA was modeled and optimized. Notably, our MC-MPPA test pieces achieved impressive sound absorption coefficients experimentally of over 0.8 in the whole frequency ranges of [397–1000] and [698–1895] Hz. The absorber’s thickness is a mere 47 mm, equivalent to 1/18.2 and 1/10.5 of the sound wavelength at the minimum operational frequency, respectively. Theoretically, with a maximum sub-chamber depth of just 20 mm, average absorption coefficient values of 0.6780 and 0.6483 were observed in [200–3000] and [200–4000] Hz ranges, respectively. Our optimization algorithm permits the definition of practical geometric parameters, promising substantial industrial benefits. The results have been validated theoretically, numerically, and experimentally.
PUBLISHED
Keywords: Porous media; 3D printing; Metamaterials; Analog circuits; Acoustic phenomena; Acoustical properties; Sound absorbers